The Influence of Viral Marketing and Consumer Engagement on Purchase Intention of Fashion Products on TikTok Shop - Dera Eka Safitri; Nindi kusnaedi; Siska Ernawati Fatimah; Soesanty Maulany (Universitas KH. Abdul Chalim Mojokerto, 2025)
High expectations for TikTok Shop as an e-commerce platform that can increase sales, but in reality, an average of around 1.2% complete transactions, resulting in a relatively low conversion rate. The focus of this research study is whether viral marketing and consumer engagement affect the purchase intention of fashion products on TikTok Shop. This study was conducted in Cirebon City with the research period in May 2025. The research variables studied are viral marketing (X1), consumer engagement (X2), and purchase intention (Y). The population of the city of Cirebon aged 20 to 41 years is set as the research population with a size of 134,143 individuals, and the sample size used is 399 individuals. This research study is classified as a quantitative study and the analysis used is Partial Least Square Structural Equation Modeling (SEM-PLS) with analysis conducted using SmartPLS. The results of the study show that all indicators meet the validity and reliability requirements suitable for analysis. The direct effect of X1 on Y is 0.220, which means an increase of one unit in X1 can increase Y by 22%, and the direct effect of X2 on Y is 0.608, which means an increase of one unit in X2 can increase Y by 60.8%. The hypothesis testing accepted that there is an influence between X1 and X2 on Y. The proportion of influence is on the coefficient of determination, which is 0.581 or 58.1%, meaning that about 41.9% is influenced by other factors.